An enquiry into the prevalence of musculoskeletal disorders and ergonomic risk factors among Hamadan-based bakers in 2017 - Majid Motamedzade Torghabeh; Javad Torkaman; Seyed Qavamedin Attari; Bahman Golzar Khojasteh; Mohammad Ebrahim Ghafari; Ali Saadatfar (مجله دانشگاه علوم پزشکی بیرجند, 2018)
Background and Aim: Musculoskeletal disorders stand as the most common work-related problem in many developing and industrial countries. This study aimed to investigate the prevalence of musculoskeletal disorders and to assess ergonomic risk factors among traditional bread bakers. Materials and Methods: This descriptive-analytic, cross-sectional study was conducted on 129 traditional bread bakers in Hamadan in February 2017. The prevalence of musculoskeletal disorders was assessed using the Nordic questionnaire, body map, and Visual Analogue Scale. The ACGIH-HAL method was used to assess hand activity level and hand maximum acceptable strength. Analysis of data was performed in SPSS (version 20) using Chi-square and independent T tests. Results: The mean and standard deviation of tenure, height, weight, BMI, and age were, respectively, 4±6.82 (year), 1.6±0.08 (m), 60±12.76 (kg), 24.65±4.70 and 43.5±12.60 (year). The organs involved in baking consisted of the neck, shoulders, back, waist, elbow, arm, hand, thigh, knee, shin and ankle. The highest prevalence rates of pain in workers referred, respectively, to the middle back (n=38; %92.68), knees (n=33; %80.49), shoulders (n=13; %30.95), forearms (n=11; %26.19), and wrists (n=11; %26.19). The prevalence of musculoskeletal disorders correlated significantly with BMI and tenure (P <0.05). Conclusion: Musculoskeletal disorders of the knees, the middle and lower back, shoulders and wrists are of a high prevalence among bakers of traditional bread. Therefore, both engineering and management interventions are recommended to eliminate musculoskeletal disorders.